Therapeutic Effects of Ziziphus mauritiana Leaves Extract on Aluminium Chloride and D-Galactose Induced Cognitive Impairment on the Brain of Wistar Rats: Histological and Biochemical Approach - Mahdi, Onesimus; Muhammad, Aisha Ibrahim; Nuhyite, Joshua Rhoda; Bobbo, Khadijat Abubakar; Gambo, Gad; Aliyu, Lawan Ibrahim; Joseph, Hosea; Zubairu, Galadima Mercy; Bhlyakamsu, Yusuf; Sodiga, Dleve Peter (Asian Journal of Science, Technology, Engineering, and Art, 2025)
Neurodegenerative disorders represent a significant and escalating global healthcare challenge, characterized by the progressive degeneration of neurons and a consequent decline in cognitive and motor functions. Among older adults, Alzheimer’s disease (AD) is the most prevalent neurodegenerative condition, marked by hallmark neuropathological features such as intracellular hyperphosphorylated tau (p-tau) forming neurofibrillary tangles, synaptic dysfunction, neuronal loss, and extracellular amyloid beta (Aβ) plaque accumulation. Aluminium (Al), a known neurotoxic metal, can cross the blood-brain barrier and accumulate in brain tissue, inducing changes associated with neurodegeneration. Additionally, D-galactose (D-gal) is frequently used in animal models to accelerate aging by inducing oxidative stress and inflammation, thus serving as a valuable tool in anti-aging and neurodegenerative research. This study investigates the therapeutic potential of Ziziphus mauritiana extract (ZME), a traditional medicinal plant with recognized nutritional and pharmacological value, in mitigating cognitive dysfunction induced by Aluminium Chloride (AlCl₃) and D-galactose in Wistar rats. Thirty-five healthy adult male rats (80–120 g) were administered D-gal (60 mg/kg, intraperitoneally) and AlCl₃ (200 mg/kg, orally) to induce neurodegeneration. Two experimental groups received ZME at doses of 100 mg/kg and 50 mg/kg, respectively, while the positive control group was treated with donepezil (1 mg/kg). Cognitive function was assessed using the Novel Object Recognition (NOR) test, oxidative stress was evaluated via Superoxide Dismutase (SOD) activity, and histological examination of the prefrontal cortex was conducted to assess neuronal integrity. Results revealed that exposure to AlCl₃ and D-gal significantly impaired cognitive performance, reduced SOD levels (p < 0.05), and induced morphological alterations in the prefrontal cortex. Treatment with ZME significantly improved cognitive performance, elevated SOD activity, and restored cortical architecture, indicating neuroprotective effects. These findings support the potential of Ziziphus mauritiana as a therapeutic agent for mitigating AD-related cognitive impairments through its antioxidative and neuroprotective mechanisms.